Growing Potentials for Migration Research using the German Socio-Economic Panel Study - Jannes Jacobsen; Magdalena Krieger; Felicitas Schikora; Jürgen Schupp (Jahrbücher für Nationalökonomie und Statistik, 2021)
This article highlights the potentials for migration research using the German Socio-Economic Panel Study (SOEP), a longitudinal panel dataset of private households in Germany running since 1984. We provide a concise overview of its basic features, describe the survey contents and research potentials, and demonstrate opportunities to link external data sources to the SOEP thereby presenting its diverse and impactful applications in migration research.
Keywords: C8; D04; D01; F22; J1; J2; J6; O15; R23; 330; Panel data; Socio-economic panel; Migration; Refugess; Integration